A suspected parasite spill-back of two novel Myxidium spp. (Myxosporea) causing disease in Australian endemic frogs found in the invasive Cane toad. - Ashlie Hartigan; Ivan Fiala; Iva Dyková; Miloslav Jirků; Ben Okimoto; Karrie Rose; David N Phalen; Jan Šlapeta (PLoS ONE, 2011)
Infectious diseases are contributing to the decline of endangered amphibians. We identified myxosporean parasites, Myxidium spp. (Myxosporea: Myxozoa), in the brain and liver of declining native frogs, the Green and Golden Bell frog (Litoria aurea) and the Southern Bell frog (Litoria raniformis). We unequivocally identified two Myxidium spp. (both generalist) affecting Australian native frogs and the invasive Cane toad (Bufo marinus, syn. Rhinella marina) and demonstrated their association with disease. Our study tested the identity of Myxidium spp. within native frogs and the invasive Cane toad (brought to Australia in 1935, via Hawaii) to resolve the question whether the Cane toad introduced them to Australia. We showed that the Australian brain and liver Myxidium spp. differed 9%, 7%, 34% and 37% at the small subunit rDNA, large subunit rDNA, internal transcribed spacers 1 and 2, but were distinct from Myxidium cf. immersum from Cane toads in Brazil. Plotting minimum within-group distance against maximum intra-group distance confirmed their independent evolutionary trajectory. Transmission electron microscopy revealed that the brain stages localize inside axons. Myxospores were morphologically indistinguishable, therefore genetic characterisation was necessary to recognise these cryptic species. It is unlikely that the Cane toad brought the myxosporean parasites to Australia, because the parasites were not found in 261 Hawaiian Cane toads. Instead, these data support the enemy-release hypothesis predicting that not all parasites are translocated with their hosts and suggest that the Cane toad may have played an important spill-back role in their emergence and facilitated their dissemination. This work emphasizes the importance of accurate species identification of pathogens relevant to wildlife management and disease control. In our case it is paving the road for the spill-back role of the Cane toad and the parasite emergence.